Partial Calcanectomy Facilitates Wound Closure of Heel Defects in High-Risk Patients. Issue 6 (June 2016) - Lin, Chin-Ta; Chen, Shyi-Gen; Chen, Tim-Mo; Chang, Shun-Cheng
Abstract : Background: Heel ulcers in patients with severe peripheral artery occlusive disease represent a challenge to the treating physician. They become more difficult to treat with underlying medical comorbidities. The purpose of this report is to document evidence that partial calcanectomy is simple to perform and clears infected bone, tissue, and ulceration. Materials: Between July 2011 and August 2013, 30 consecutive patients presented to our department with heel wounds caused by diabetes mellitus and pressure. After evaluation by a vascular surgeon, 12 patients diagnosed with near total occlusive peripheral vascular disease were included in this report. Of the 12 patients, 7 were women. Their ages ranged from 65 to 79 years (mean, 73.3 years). After admission, surgical debridement was performed emergently with subsequent partial calcanectomy and wound closure. Results: Eight heel wounds (75%) healed completely with no further surgery to achieve defect coverage. Wound dehiscence developed in 4 patients (25%). The mean number of debridements was 1.75 (range, 1–3) with a total operation time of 71.5 minutes (range, 45–114 min). One patient died of acute myocardial infarction 2 weeks after discharge. The mean length of hospital stay was 8.3 days (range, 5–16 days). Conclusion: In this study, we demonstrate that partial calcanectomy is practical for the treatment of plantar heel ulcers in patients with severe comorbidities. With proper surgical planning and postoperative care, partial calcanectomy is a viable alternative to below-the-knee amputation and may better serve the patient who would otherwise be restricted to a sedentary lifestyle.